2 - Perceived Threat of Malaria and the Use of Insecticide Treated Bed Nets in Nigeria - Ali Arazeem Abdullahi; Cecilia Van Zyl-Schalekamp; Anton Seneka (African Sociological Review, 2014)
Using multiple qualitative methods, this study investigated the perceived threat and perceived susceptibility of children under five years of age to malaria, and willingness of the caregivers to use the ITNs in the prevention of malaria in selected rural and urban areas of Nigeria. The health belief model (HBM) is the theoretical anchor of the study. Samples included mothers, fathers and grandparents whose child/ward had manifested malaria symptoms at one time or another and who had reported or failed to report such cases at the available health centres. Other respondents were community leaders, health workers and traditional pharmacists popularly known as elewe-omo. The study found that malaria was perceived as a serious health problem and a threat to the children by the majority of the respondents. However, high perceived threat of malaria did not guarantee widespread use of the ITNs owing to limited access and poor distribution networks. Some measures for equitable and sustainable distribution and use of the ITNs in local communities have been recommended.